Toxicity of immune checkpoint inhibitors and tyrosine kinase inhibitor combinations in solid tumours: a systematic review and meta-analysis - O’Reilly, David; O’Leary, Caroline L.; Reilly, Aislinn; Teo, Min Yuen; O’Kane, Grainne; Hendriks, Lizza; Bennett, Kathleen; Naidoo, Jarushka (Frontiers in Oncology, 2024)
The combination of immune checkpoint inhibitors (ICIs) and tyrosine kinase inhibitors (TKIs) can be associated with significant toxicity. We performed a systematic review and meta-analysis of the toxicity of combination treatment of ICIs with TKIs (ICI + TKI) in clinical trials with solid organ malignancies. Our primary endpoint explored the incidence of grade 3 - 5 (G3-5) treatment-related toxicity and our secondary endpoints included the incidence of toxicity by treatment type, disease type and studies with run-in strategies. A total of 9750 abstracts were identified, of which 72 eligible studies were included. The most common disease types were non-small cell lung cancer (n=8, 11.1%), renal cell carcinoma (n=10, 13.8%) and hepatobiliary cancers (n=10, 13.8%). The overall incidence of G3-5 toxicity was 56% (95% CI = 50% – 61%). The most common TKIs combined with ICIs in this analysis were multi-targeted TKIs (n = 52, 72%), VEGF specific (n = 9, 12.5%), or oncogene-targeting TKIs (EGFR, ALK, BRAF, MEK) (n =11, 15.3%). Oncogene-targeted TKIs were associated a higher incidence of rashes and immune related adverse events (irAEs) and lower incidence of hypertension. In studies which used a TKI ‘run-in’ to mitigate toxicity, the pooled estimate of G3-5 toxicity was 71% (95% CI 57-81%). Almost half of studies (48%) omitted the incidence of G3-5 irAEs. Our work suggests that the majority of patients who receive ICI-TKI combinations will experience high grade toxicity (G3-G5) and that toxicity may be specific to TKI partner (Oncogene targeted TKIs: Rash, irAEs; VEGF/Multitargeted: Hypertension). These data did not suggest that a TKI ‘run-in’ was associated with a lower incidence of G3-5 toxicity. Reporting of irAEs was inconsistent supporting the need for harmonisation of adverse event reporting to include onset, duration and treatment. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022367416.